Yellow nail syndrome: a series of two clinical cases and review of the literature - Tatyana A. Gosteva; Victoria M. Kleuzovich; Roman V. Saraniuk (Vestnik Dermatologii i Venerologii)
Yellow nail syndrome is a rare disease of unknown etiology, characterized by damage to the lung parenchyma and nail apparatus. The etiopathogenesis of the disease remains unclear. There are no precise epidemiological data on the disease due to its low incidence. The clinical picture that allows one to suspect this disease is a combination of changes in the color of the nail plates, lymphedema and such pulmonary manifestations as the presence of bronchiectasis, chronic bronchitis, sinusitis, recurrent pleural effusion, pneumonia, disseminated processes in the lungs. Yellow nail syndrome is a serious interdisciplinary problem in terms of both diagnosis and therapy of this group of patients. There are no approved treatments for yellow nail syndrome. This disease can resolve on its own within a few months if it is not associated with any paraneoplastic syndrome. The article presents a series of two clinical cases with an established diagnosis of yellow nail syndrome, highlights currently known data on the etiopathogenesis and clinical picture of the disease, and examines issues of its diagnosis and treatment.